Numerical Study on the In-Plane and Out-of-Plane Resistance of Brick Masonry Infill Panels in Steel Frames - Vahid Bahreini; Tariq Mahdi; MohammadMahdi Najafizadeh (Shock and Vibration)
Masonry infill walls are one of the main forms of interior partitions and exterior walls in many parts of the world. Nevertheless, serious damage and loss of stability of many masonry infill walls had been reported during recent earthquakes. To improve their performance, the interaction between these infill walls and the bounding frames needs to be properly investigated. Such interaction can dramatically increase the stiffness of the frame in the in-plane direction. To avoid the negative aspects of inappropriate interactions between the frame and infill wall, some kind of isolation needs to be introduced. In this paper, three different configurations have been evaluated by using the general finite element software, ABAQUS. Nonlinear pushover and time history analyses have been conducted for each of the three configurations. Results showed that isolation of the infill from the frame has a significant effect on the in-plane response of infilled frames. Furthermore, adequate out-of-plane stability of the infill wall has been achieved. The results show that masonry infill walls that have full contact at the top of the wall but isolated from columns have shown acceptable performance.